Peripheral Auditory Pathway and ABR Characterization in Adults with Williams Syndrome - Nascimento, Jacqueline Aquino do; Silva, Liliane Aparecida Fagundes; Samelli, Alessandra Gianella; Matas, Carla Gentile (International Archives of Otorhinolaryngology, 2024)
Introduction Williams syndrome (WS) is a genetic disorder caused by a microdeletion in chromosome 7, affecting ∼ 28 genes. Studies have demonstrated conductive losses seemingly related to the absence of the elastin gene and mild to profound sensorineural losses due to cochlear fragility.Objective To characterize and compare the peripheral auditory system and auditory brainstem response (ABR) of adults with WS and neurotypical adults matched by age and gender.Methods We conducted a cross-sectional observational study with 30 individuals of both sexes, aged 18 to 37 years – 15 of them with WS (study group) and 15 with neither the syndrome nor hearing complaints (control group), matched for sex and age. The subjects underwent pure-tone and speech audiometry, acoustic immittance, transient-evoked otoacoustic emissions (TEOAEs), and ABR.Results Early-onset sensorineural hearing loss was found in 53.3% of the study sample, mostly mild, occurring above 3 kHz. The TEOAEs were absent in 53.3% of assessed subjects; for those in whom they were present, the signal-to-noise responses were significantly lower than in the control group. In the ABR, increased absolute latencies were observed in waves I and III.Conclusion Individuals with WS have early and progressive cochlear impairments, mainly affecting the basal region of the cochlea. They may have low brainstem changes which seem to begin in adulthood.
Keywords: Williams syndrome; hearing; hearing loss